THE INFLUENCE OF SOIL TEXTURE TYPES ON LAND RESILIENCE TO DROUGHT IN SOUTH NIAS - Harefa, Darmawan (Jurnal Sapta Agrica, 2025)
This study aims to analyze the influence of soil texture types on land resilience to drought in South Nias, with a focus on the soil's capacity to retain moisture during prolonged dry seasons. The collected data include soil texture types (sand, silt, clay, and loam) and physical soil properties that affect water retention. The results indicate that sandy soils have low water-holding capacity, making them highly vulnerable to drought. In contrast, clay soils, while having high water retention, often face poor drainage issues. Loamy soils, which are a mixture of sand, silt, and clay, demonstrate better drought resilience due to a balanced capacity for water retention and drainage. The study also highlights the importance of soil management strategies tailored to soil texture types to enhance land resilience to drought. These include mulching, drip irrigation, and increasing organic matter content. Based on these findings, the application of more effective soil conservation techniques is recommended to support sustainable agriculture in South Nias.